International relations scholarship around the world (2009)
It has become widely accepted that the discipline of International Relations (IR) is ironically not 'international' at all. IR scholars are part of a global discipline with a single, shared object of study - the world, and yet theorizing gravitates around a number of concepts that have been conceived solely in the United States. The purpose of this book is to re-balance this 'western bias' by examining the ways in which IR has evolved and is practiced around the world. The fifteen case studies offer fresh insights into the political and socioeconomic environments that characterize diverse geocultural sites and the ways in which these traits inform and condition scholarly activity in International Relations. By bringing together scholars living and working across the globe Tickner and Wæver provide the most comprehensive analysis of IR ever published. It is essential reading for anyone who is concerned about the history, development and future of international relations.